Monitoring and Information System for Automatic Clothes Drying Based on the Internet of Things - Mila Mila; Ahmad Taqwa; Suroso Suroso (LPPM Universitas Islam 45 Bekasi, 2024)
This research develops an Internet of Things (IoT)-based automatic clothes drying monitoring and information system to overcome the challenges of drying clothes due to uncertain weather changes. The system integrates NodeMCU ESP8266 as the main controller with various sensors such as rain, light, temperature, and humidity sensors to detect environmental conditions. The servo motor is used as a driving force to move the clothesline. The smartphone-based user interface was developed using the MIT App Inventor to enable remote monitoring and control. The test results showed that the system successfully detected weather changes and responded automatically, providing real-time information to users. Implementing IoT technology in this system allows for more efficient and practical management of clotheslines, overcoming the limitations of conventional drying methods.